HLY1104 Winter Cruise Zooplankton Genetics (Arctic Data Center, 2014)
The files contain mitochondrial gene sequence data for individual zooplankton collected in the Bearing, Beaufort, and Chukchi seas during early winter, November December, 2011 on the USCGC Healy (HLY1104). The files are Fasta files that can be opened in most bioinformatics software programs (e.g. Geneious, MegAlign, MEGA) or text/word processing programs. For each sequence, the file contains the cruise number, isolate number, and station number followed by the mt COI genetic sequence. A separate readme file contains the station information